2021
DOI: 10.3389/fphar.2021.703985
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of Flavones-Rich Fraction From Arrabidaea chica Verlot (Bignoniaceae)

Abstract: Acknowledging the need of identifying new compounds for the treatment of leishmaniasis, this study aimed to evaluate, from in vitro trials, the activity of flavones from Arrabidaea chica against L. amazonensis. The chromatographic profiles of the hydroethanolic extract and a flavone-rich fraction (ACFF) from A. chica were determined by high-performance liquid chromatography coupled with a diode-array UV-Vis detector (HPLC-DAD-UV) and electrospray ionization mass spectrometry in tandem (LC-ESI-MS-MS). The flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Previous studies demonstrated a direct effect of A. chica against L. amazonensis and L. infatum promastigote forms [ 20 , 21 ]. Our research group reported that A. chica was able to inhibit the proliferation of promastigote forms of L. amazonensis [ 11 , 12 , 22 ]. Moreover, we verified a superiority of carajurin among the other anthocyanidins in inhibiting Leishmania promastigotes, demonstrating the direct action of this natural compound on this parasite [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated a direct effect of A. chica against L. amazonensis and L. infatum promastigote forms [ 20 , 21 ]. Our research group reported that A. chica was able to inhibit the proliferation of promastigote forms of L. amazonensis [ 11 , 12 , 22 ]. Moreover, we verified a superiority of carajurin among the other anthocyanidins in inhibiting Leishmania promastigotes, demonstrating the direct action of this natural compound on this parasite [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…105 Furthermore, flavones showing anti-leishmanial potential have been described in the literature, 106 whereas apigenin (PubChem CID: 5280443) and luteolin (PubChem CID: 5280445) have shown the potential of inhibiting the growth of L. amazonensis. 107 Limitations of the present study should be also mentioned, such as the protein dynamics and complex stabilities with MDS lasting within nanoseconds scales (0-100 ns), while most structural dynamics and biological activities of proteins occur within timescales of microseconds and milliseconds. 108 Even so, complex dynamics and interactions between enzymes and ligands have been reported using nanosecond timescales.…”
Section: Discussionmentioning
confidence: 92%
“…The IC 50 values of all compounds tested were calculated from the total of intracellular amastigote from 100 cells. Parameters of infection analysis were performed according to Silva-Silva et al. (2021a) .…”
Section: Methodsmentioning
confidence: 99%